O espectro de escalares do mecanismo seesaw triplo - Caetano, Wellington de Lima (2011)
In this thesis we study some extensions of the Standard Model to accommodate mass for neutrinos. In order to explain the deficit of atmospheric and solar neutrinos observed on Earth, the phenomenon of flavor oscillation between families requires that neutrinos have physical mass eigenstates. For this, we constructed possible mass terms of Majorana or Dirac. We also develop type I-II seesaw mechanisms to generate neutrino masses. Analyzing the applicability of these seesaw mechanisms, we observe, for example, that the type I seesaw requires the existence of heavy right-handed neutrinos mass with the scale of grand unification. Next, we study the triple seesaw mechanism, where we show the possibility of generating neutrino mass using the TeV energy accelerators. We also examine the scalar sector of this mechanism, which is based on a Two Higgs Doublet Model, in addition to standard model content. Finally, we derive the mass spectrum of the scalar, obtaining a stable pseudoscalar with mass close to 10 GeV, as a possible cold dark matter candidate.